Drinking Water Facilities and Hygiene Behavior on the Incidence of Diarrhea in Toddlers in North Jakarta City - Maulida Khairunnisa; Tri Joko; Mursid Raharjo (Gema Lingkungan Kesehatan, 2024)
North Jakarta City is a Coastal Area in the Province of DKI Jakarta. Data from 2017-2021 shows that diarrhea cases in toddlers in North Jakarta City have fluctuated over a 5-year period, with more than 15,000 cases each year. Drinking water facilities that meet health requirements only reach 37.01%. This study aims to analyze the risk factors for the incidence of diarrhea in toddlers in North Jakarta City. This study uses a cross-sectional study design with a sample size of 112 samples taken using cluster sampling technique. The variables examined in the study are the incidence of diarrhea in toddlers, total bacteriological quality of E.coli in water, quality of water storage places, household drinking water treatment, food hygiene sanitation conditions, and handwashing behavior of mothers/caregivers. Data were processed and analyzed descriptively as well as hypothesis testing using chi-square test and multiple logistic regression analysis using the backward: Likelihood Ratio (LR) method. The results showed that the bacteriological quality of total E.coli in water that did not meet the requirements, household drinking water treatment, and handwashing behavior with soap of mothers/caregivers are risk factors for the incidence of diarrhea in toddlers. Therefore, increasing the knowledge and skills of mothers/caregivers and monitoring the quality of household drinking water are needed to prevent and address diarrhea in toddlers.